Proceedings of the Tenth International Conference on Management Science and Engineering Management - Xu, Jiuping; Hajiyev, Asaf.; Nickel, Stefan; Gen, Mitsuo; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2017)
This book presents the proceedings of the Tenth International Conference on Management Science and Engineering Management (ICMSEM2016) held from August 30 to September 02, 2016 at Baku, Azerbaijan and organized by the International Society of Management Science and Engineering Management, Sichuan University (Chengdu, China) and Ministry of Education of Azerbaijan. The aim of conference was to foster international research collaborations in management science and engineering management as well as to provide a forum to present current research findings. The presented papers were selected and reviewed by the Program Committee, made up of respected experts in the area of management science and engineering management from around the globe. The contributions focus on identifying management science problems in engineering, innovatively using management theory and methods to solve engineering problems effectively and establishing novel management theories and methods to address new engineering management issues.
Keywords: EXTC Engineering; Operations Research/Decision Theory; Communications Engineering, Networks; Engineering Economics, Organization, Logistics, Marketing